URGENSI BANK SAMPAH DALAM MENCIPTAKAN KEBERSIHAN LINGKUNGAN DALAM PRESPEKTIF PENDIDIKAN ISLAM - Nur Khamim; Moh. Syamsi (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2021)
A clean environment is a prerequisite in creating tranquility, and environmental beauty that has an impact on the soul. Waste management is a problem that makes the environment can not be clean and beautiful. One solution in waste management is a waste bank. The concept of garbage banks began to be realized in the village of Manyarejo on Jl. Satelit III RT.01 RW.01 which was socialized by PUSDA Kota about environmental issues and greening programs, and triggered the name